Extracorporeal Shock Wave Therapy for the Treatment of Non-Union of a Canine Mandibular Fracture - Oginska, Olivia J.; Whitelock, Richard; Hausler, Kirsten; Stelman, Amy; Allen, Matthew J. (VCOT Open, 2019)
The use of extracorporeal shock wave therapy (ESWT) for the treatment of delayed or non-union of long bone fractures has been described in human patients with encouraging results. This case report describes the successful treatment of a mandibular fracture non-union with ESWT. To authors' knowledge, this is the first report of the clinical use of ESWT for the management of a non-union in a dog.
Keywords: fracture healing; extracorporeal shock wave; non-union; mandible; dog